The future looks like the past: Introgression of domesticated Atlantic salmon escapees in a risk assessment framework. Issue 6 (3rd June 2020) - Glover, Kevin A.; Wennevik, Vidar; Hindar, Kjetil; Skaala, Øystein; Fiske, Peder; Solberg, Monica F.; Diserud, Ola H.; Svåsand, Terje; Karlsson, Sten; Andersen, Lasse B.; Grefsrud, Ellen S.
Abstract: Escapes of domesticated fish from aquaculture, followed by interbreeding with wild conspecifics, represent a threat to the genetic integrity and evolutionary trajectory of natural populations. Approximately fifty years of Atlantic salmon production has left an unprecedented legacy of widespread introgression of domesticated escapees in wild Norwegian populations. A major question, however, is whether current aquaculture practice will lead to additional introgression in the near future. As part of the updated Norwegian risk assessment of fish farming, we conducted a risk assessment for further introgression of domesticated escapees in wild populations in Norway. Extensive data of reported numbers of escapees, observed proportions of escapees in rivers, removal of escapees pre‐spawning, and the resilience of wild populations through demographic and genetic status informed the risk assessment. The analysis revealed that rivers in 10 of the 13 aquaculture production zones covering Norway display a moderate or high risk of further introgression of domesticated escapees. This comes in addition to widespread introgression that is already documented. We therefore conclude that so long as aquaculture production continues at its present level and form, there is a moderate‐to‐high risk of further introgression of domesticated salmon in many native populations throughout much of Norway.